2011
DOI: 10.2337/dc10-1925
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Degludec in Type 1 Diabetes

Abstract: OBJECTIVEInsulin degludec (IDeg) is a basal insulin that forms soluble multihexamers after subcutaneous injection, resulting in an ultra-long action profile. We assessed the efficacy and safety of IDeg formulations administered once daily in combination with mealtime insulin aspart in people with type 1 diabetes.RESEARCH DESIGN AND METHODSIn this 16-week, randomized, open-label trial, participants (mean: 45.8 years old, A1C 8.4%, fasting plasma glucose [FPG] 9.9 mmol/L, BMI 26.9 kg/m2) received subcutaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 16 publications
10
133
0
4
Order By: Relevance
“…Several studies in adults have shown that IDeg exhibits the desired optimal pharmacokinetic properties and confers a low risk of hypoglycemia in patients with both type 1 and type 2 diabetes [9][10][11]16]. In addition, the majority of the studies have reported comparable glucose-lowering effects of IDeg and IGlar in patients with type 1 diabetes, as demonstrated by equivalent FPG and HbA1c levels [9,13,[17][18][19]. As mentioned in the introduction, in a 26-week study of pediatric patients with type 1 diabetes of all ages, Thalange et al [13] reported the non-inferiority of IDeg as compared with IDet in regard with changes in HbA1c levels from the baseline.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Several studies in adults have shown that IDeg exhibits the desired optimal pharmacokinetic properties and confers a low risk of hypoglycemia in patients with both type 1 and type 2 diabetes [9][10][11]16]. In addition, the majority of the studies have reported comparable glucose-lowering effects of IDeg and IGlar in patients with type 1 diabetes, as demonstrated by equivalent FPG and HbA1c levels [9,13,[17][18][19]. As mentioned in the introduction, in a 26-week study of pediatric patients with type 1 diabetes of all ages, Thalange et al [13] reported the non-inferiority of IDeg as compared with IDet in regard with changes in HbA1c levels from the baseline.…”
Section: Discussionmentioning
confidence: 87%
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A total of 4275 patients were administered Degludec (1102 with T1DM and 3173 with T2DM). It was confirmed that a decrease in HbA 1c was the same in all trials in terms of all the compared products (insulin Detemir and insulin Glargine) [12][13][14].…”
Section: New Basal Insulinmentioning
confidence: 52%
“…Przeprowadzono 11 międzynarodowych, kontrolowanych, otwartych, randomizowanych, z grupami równoległymi, prowadzonych do osiągnięcia zakładanego celu, badań klinicznych trwających 26 lub 52 tygodnie, w których 4275 pacjentom podawano Degludec (1102 z cukrzycą typu 1 i 3173 z cukrzycą typu 2). Potwierdzono, że obniżenie HbA 1c było równoważne we wszystkich badaniach w odniesieniu do wszystkich produktów porównywanych (insulina Detemir i insulina Glargina) [12][13][14]. W metaanalizie obejmującej siedem badań prowadzonych do osiągnięcia zakłada-nego celu (treat to target) u pacjentów z cukrzycą typu 1 i typu 2 Degludec okazał się być skuteczniejszy pod względem mniejszej liczby potwierdzonych epizodów hipoglikemii wynikającej z leczenia i potwierdzonych hipoglikemii nocnych w porównaniu z insuliną bazową Glargina.…”
Section: Nowe Insuliny Bazoweunclassified